Tinea Corporis Therapy - Inneke Kusumawati Susanto (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2023)
Tinea corporis is one of the skin diseases caused by dermatophyte fungi and is a fairly common disease caused by Trichophyton species. Tinea corporis mainly occurs in tropical countries or regions such as Southeast Asia and North America. Patients with tinea corporis usually have high activities and actively sweat. Tinea corporis has typical symptoms, i.e. the presence of patches of erythematous plaque that are circumscribed, round or oval shapes, and common predilection in the body trunk. Therapy of tinea corporis disease can use topical antifungals such as clotrimazole, ketoconazole, miconazole, naphthyline, and terbinafine. In cases of systemic infection, oral antifungals such as terbinafine, itraconazole, fluconazole, and griseofulvin can be drugs of choice. Appropriate treatment of tinea corporis gives a good prognosis and prevents resistance and recurrence.